2002
DOI: 10.1002/art.10581
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and complete resolution of proteinuria due to renal amyloidosis in a patient with rheumatoid arthritis treated with infliximab

Abstract: We describe herein a patient with rheumatoid arthritis who developed proteinuria due to AA amyloidosis, in whom the inflammatory disease was rapidly and completely suppressed by treatment with infliximab. This response was accompanied by resolution of the proteinuria and stabilization of the amyloid deposits as seen on serial 123I‐labeled serum amyloid P scintigraphy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 12 publications
1
37
0
5
Order By: Relevance
“…Proteinuria decreases rapidly after treatment that eliminates or markedly reduces production of the amyloidogenic precursor protein. In AL disease, this observation has been made after high-dose chemotherapy that eliminates the clonal plasma cells that produce the monoclonal amyloidogenic light chain (51,52) and in AA disease, when the underlying inflammatory disease becomes quiescent (53)(54)(55). Similar to the proBNP response in cardiac amyloidosis, the reduction in proteinuria occurs in many patients before substantial degradation of existing amyloid deposits would be expected to occur (2).…”
Section: How Does Amyloidosis Cause Renal Disease?mentioning
confidence: 99%
“…Proteinuria decreases rapidly after treatment that eliminates or markedly reduces production of the amyloidogenic precursor protein. In AL disease, this observation has been made after high-dose chemotherapy that eliminates the clonal plasma cells that produce the monoclonal amyloidogenic light chain (51,52) and in AA disease, when the underlying inflammatory disease becomes quiescent (53)(54)(55). Similar to the proBNP response in cardiac amyloidosis, the reduction in proteinuria occurs in many patients before substantial degradation of existing amyloid deposits would be expected to occur (2).…”
Section: How Does Amyloidosis Cause Renal Disease?mentioning
confidence: 99%
“…Few case reports and studies in the literature indicate that anti-TNF-alpha agents could be effective in this regard. Elkayam et al 10 reported a 39-year-old patient with secondary amyloidosis because of RA, whose proteinuria was controlled completely after infliximab therapy. Nakamura et al 11 studied 14 patients with AA-type amyloidosis secondary to RA and observed significant improvement in activity markers (DAS28-ESR, CRP, and SAA) and proteinuria; they also indicated that patients with serum creatinine levels less than 2 mg/dL before therapy showed better response.…”
Section: Discussionmentioning
confidence: 99%
“…[17] The treatment with infliximab was demonstrated to be effective in the resolution of proteinuria resulting from renal amyloidosis in a patient with rheumatoid arthritis. [18] Metyas et al [19] reported a case with renal amyloidosis secondary to FMF who was successfully treated with anti-TNF therapy. In the present case, there was not a significant improvement in renal functions and resolution of proteinuria with anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%